Pengaruh Tipe Kepribadian Dan Perilaku Konsumtif Terhadap Perencanaan Keuangan Pribadi Mahasiswa - Kafidin Muzakki (.Universitas PGRI Adi Buana, 2023)
This study aims to determine the effect of personality type and. Consumptive Behavior towards Personal Financial Planning. The research method used is quantitative method and the data analysis used in this study includes classical assumption testing, multiple linear regression analysis, and hypothesis testing with simultaneous test (F-test) and partial test (t-test) using SPSS. The results showed that the variables of Personality Type and Consumptive Behavior had a simultaneous effect on Personal Financial Planning. The results of the Personality Type variable have a partially significant positive effect on personal financial planning, while consumptive behavior has a partially significant negative effect on personal financial planning.